KEMAMPUAN MENULIS DESKRIPSI SISWA KELAS VIII SMP NEGERI 16 BANDARLAMPUNG TAHUN PELAJARAN 2012/2013 - dery oscar; iqbal hilal; nurlaksana eko rusminto (Jurnal Kata (Bahasa, Sastra, dan Pembelajarannya), 2013)
Issues addressed in this study is how the ability of students to write descriptions of the sights you've visited the eighth grade students of SMP Negeri 16 Bandarlampung Academic Year 2012/2013. The purpose of this research was to determine the ability of students to write descriptions of the sights you've visited in the eighth grade students of SMP Negeri 16 Bandarlampung in the academic year 2012/2013.           The method used in this research is descriptive quantitative. The population in this study amounted to 204, spread into 6 classes, while the sample in this study is 36 students. The aspect of the assessment are 1) compliance with the contents of the title, 2) the use of spelling and writing, 3) choice of words or diction, 4) sentence structure, 5) integration of each sentence, 6) integration between paragraphs, 7) the overall content, and 8) neatness, of each of these aspects the highest score of 100.          Based on these results, the ability to write descriptions of eighth grade students of SMP Negeri 16 Bandarlampung has done quite enough got a score of 73.33 for the interval 60-74 lowest score obtained by the students is 63 which is quite in the interval 60-74. In addition, of the 36 students who take the test have the ability to write descriptions there are 6 students with good, 30 students capable enough, while the average score overall writing skills test description eighth grade students of SMP Negeri 16 Bandarlampung is 71.25 with the level of ability enough.Keyword: writing skills, level, average score